2015
DOI: 10.4103/0019-5413.159595
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic corticosteroid injection in ulnar wrist pain in distal radius fracture

Abstract: Background:Ulnar sided wrist pain is one of the most common complications of distal radius fractures. The simplest method for decreasing pain for this affliction is corticosteroid injection. The present study was designed to assess the effect of corticosteroid injection in the prevention of ulnar sided wrist pain.Materials and Methods:In this clinical trial patients with distal radius fractures scheduled for closed reduction and percutaneous pin fixation were divided into control and corticosteroid groups. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…2 ). Two other small sample studies (Bogefeldt et al 2008 ; Saied et al 2015 ) of non-postoperative pain (n = 242) showed that steroids can reduce the incidence of chronic pain, but neither reported therapeutic doses (RR 0.72 [95% CI 0.54–0.96]; supplementary Fig. 3 ), results need to be interpreted with caution.…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…2 ). Two other small sample studies (Bogefeldt et al 2008 ; Saied et al 2015 ) of non-postoperative pain (n = 242) showed that steroids can reduce the incidence of chronic pain, but neither reported therapeutic doses (RR 0.72 [95% CI 0.54–0.96]; supplementary Fig. 3 ), results need to be interpreted with caution.…”
Section: Resultsmentioning
confidence: 95%
“…Of the 20 studies (3788 participants) involving nociceptive pain, 1 study evaluated both steroids and NSAIDs (in different group) (Romundstad et al 2006 ), 9 studies evaluated steroids (Turan et al 2015 ; Romundstad et al 2006 ; Bogefeldt et al 2008 ; Dojode 2012 ; Lin et al 2010 ; Spijker-Huiges et al 2014 ; Saied et al 2015 ; Mardani-Kivi et al 2015 ; Li et al 2018 ), and 12 studies evaluated NSAIDs (van Helmond et al 2016 ; Sun et al 2013 ; Romundstad et al 2006 ; Ling et al 2016 ; Fransen et al 2006 ; Comez et al 2015 ; Bugada et al 2015 ; Hancock et al 2007 ; Shin et al 2013 ; Wang et al 2014 ; Haddad et al 2019 ; Ge et al 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations